Identifying Confirmation Bias in a Search as Learning Task: A Study on The Use of Artificial Intelligence in Education - Machado, Marcelo; Souza, Jairo F. de; Siqueira, Sean W. M. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na Educação, 2024)
Confirmation bias, the tendency to favor information that supports existing beliefs, can hinder information-seeking, especially in learning contexts where it can perpetuate a one-sided perspective. This paper examines how confirmation bias affects search behaviors among 84 participants learning about AI in education. Participants were divided into Neutral and Biased groups based on their prior attitudes, with the Biased group receiving reinforcing information beforehand. Participants’ interactions with the search system were logged, and we analyzed the data for behavioral differences. Results showed that biased participants often completed searches quickly, spending less time engaging with and selecting search results, and issued longer queries. However, other variables showed no statistical difference. Some results contradict other studies on confirmation bias in search, highlighting the complexity of search dynamics in learning contexts and suggesting the need for specialized research into cognitive biases in search as a learning process.